2023
DOI: 10.55927/ijar.v2i6.4556
|View full text |Cite
|
Sign up to set email alerts
|

Development of E-Comic-Based Learning Media Using Pixton in Theme 7 Sub-theme 2 in Class V SDN 101775 Sampali T.A 2022/2023

Abstract: The purpose of this research is to produce a learning media in the form of E-Comic using Pixton which is feasible, effective and practical. The type of research used is research and development (R&D) which has a 4D development model developed by Thiagarajan namely Define, Design, Develop, and Disseminate. The instruments used to collect data were teacher interviews, material and media validation questionnaires, educational practitioner (teacher) questionnaires, and test questions for students. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Based on the results of the analysis of articles that have been collected and studied in depth by researchers, it was found that there is an influence on the use of e-comics in mathematics learning, especially in realistic mathematical approaches, able to improve students' critical thinking skills and ability in creativity. E-comic-based learning media using Pixton is declared feasible, practical, and effective to be applied in school learning (Nurmayani & Sinaga, 2023). E-comic-based mathematics learning materials are very valid and respond with high criteria so that the media developed by researchers can be used as additional teaching materials to teach multiplication and division concepts (Widyasari & Nurcahyani, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the analysis of articles that have been collected and studied in depth by researchers, it was found that there is an influence on the use of e-comics in mathematics learning, especially in realistic mathematical approaches, able to improve students' critical thinking skills and ability in creativity. E-comic-based learning media using Pixton is declared feasible, practical, and effective to be applied in school learning (Nurmayani & Sinaga, 2023). E-comic-based mathematics learning materials are very valid and respond with high criteria so that the media developed by researchers can be used as additional teaching materials to teach multiplication and division concepts (Widyasari & Nurcahyani, 2021).…”
Section: Discussionmentioning
confidence: 99%